Metode Isolasi Jamur Patogen Serangga (Aschersonia Placenta) Dengan Menggunakan Media Potato Sucrose Agar (PSA) - Ni Nyoman Putri Sartika Wangi; I Putu Sudiarta; Ketut Ayu Yuliadhi (Agriculture Faculty of Flores University, 2023)
Cultivating oranges is one of the main fruit commodities in Bali. Citrus cultivation often experiences problems, one of which is insect pests and plant diseases. Pests that often attack are whitefly. Whiteflies cause damage directly or indirectly. It directly results in stunted plant leaves because the whitefly sucks on the young shoots and leaves. Indirectly, the whitefly has been reported as a vector of various diseases caused by viruses. Based on this, it is necessary to control efforts, one of which is by using biological control of insect pathogenic fungi. The pathogenic fungus found in association with the citrus whitefly is Aschersonia placenta. The insect pathogen A. placenta naturally exists in nature and has potential as a biological control agent, however special handling is required in its utilization. One such treatment is the isolation of the fungus from the field for mass cultivation in the laboratory. Isolation poetry using Potato Sucrose Agar (PSA) was the best, of the four isolation methods performed. The method is detailed as follows: the fungal stroma is rinsed with sterile distilled water, with 70% alcohol, then rinsed again with sterile distilled water before being planted in PSA media.